1990
DOI: 10.1007/bf01189075
|View full text |Cite
|
Sign up to set email alerts
|

Structures of acidic O-linked polylactosaminoglycans on human skim milk mucins

Abstract: O-Linked glycans were isolated from human skim milk mucins or mucin-derived high-molecular weight glycopeptides and fractionated by anion exchange chromatography into neutral and acidic alditols. Major oligosaccharides contained in the acidic fraction were purified by high performance liquid chromatography and structurally characterized by a combination of fast atom bombardment mass spectrometry, methylation analysis and 500 MHz 1H-nuclear magnetic resonance spectroscopy. The structural aspects exhibited by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
57
1
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 31 publications
2
57
1
4
Order By: Relevance
“…Such a competition could underlie the reported differences in glycosylation densities, when comparing lactation-and tumor-associated glycoforms of the mucin (26). In T47D cells, no functional core2 enzyme is expressed (6), and initial O-glycosylation can proceed to completion before inhibitory glycan substituents (sialylated core1) are formed in the trans-Golgi. One of the enzymes involved in initial O-glycosylation, the recently described rGalNAc-T4, which adds GalNAc site-specifically to the DTR motif, was found to prefer substrates carrying GalNAc at the proximal sites (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a competition could underlie the reported differences in glycosylation densities, when comparing lactation-and tumor-associated glycoforms of the mucin (26). In T47D cells, no functional core2 enzyme is expressed (6), and initial O-glycosylation can proceed to completion before inhibitory glycan substituents (sialylated core1) are formed in the trans-Golgi. One of the enzymes involved in initial O-glycosylation, the recently described rGalNAc-T4, which adds GalNAc site-specifically to the DTR motif, was found to prefer substrates carrying GalNAc at the proximal sites (24).…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, the nonexpression of the core2 enzyme, Gal␤1-3GalNAc/␤-6-N-acetylglucosaminyltransferase (5), leads to the truncation of polylactosamine-type chains found on the lactation-associated mucin (6) and to the accumulation of core-type chains (2)(3)(4). The preponderance of sialylated core1-trisaccharide on carcinoma-associated MUC1, which can be regarded as a biosynthetic dead end product, has been shown to originate from the simultaneous up-regulation and overexpression of Gal␤1-3GalNAc/␣-3-sialyltransferase (7).…”
mentioning
confidence: 99%
“…1 and Ref. 8). In breast cancers and breast cancer cell lines, there is a shift toward the addition of shorter O-glycans, the degree to which this change is seen being dependent, to some extent, on the level of expression of the core 2 synthesizing enzyme, which can be totally absent (6,9).…”
mentioning
confidence: 99%
“…In many carcinomas that express membrane and secreted mucins, changes in mucin-type O-glycosylation have been documented (4). In the change to malignancy in the breast, changes in the glycosylation of the MUC1 mucin has been extensively studied, following both the composition and density of the O-glycans added (5)(6)(7)(8), and the profile of glycosyltransferases expressed (9 -13). Because MUC1 is expressed by Ͼ90% of breast cancers, the carcinoma-associated glycoforms are being considered as targets both for exogenously administered antibodies (14) and for active specific immunotherapy using MUC1-based immunogens (15,16).…”
mentioning
confidence: 99%
“…Analysis of the O-glycans attached to the mucin produced by the normal lactating breast and by breast cancer cell lines has shown that the oligosaccharides added to the normal mucin are core 2-based structures (11), whereas in the cancer-associated mucin, shorter core 1-based structures dominate (4,5,12). As illustrated in Fig.…”
mentioning
confidence: 99%